Protective effect of resveratrol on retinal damage in glaucoma: a systematic review and meta-analysis of preclinical studies - Zhang, Feng; Li, Tao; Wan, Junli; Wang, Lu; Guo, Wenmei; Hu, Yue; Wang, Hao; Bian, Wei (Frontiers in Pharmacology, 2025)
IntroductionResveratrol, a polyphenolic compound commonly found in natural plants and fruits, exhibits potential in preventing optic nerve damage in glaucoma, as indicated by several animal studies. However, there is presently a dearth of relevant evidence available for comprehensive summarization.MethodsIn this study, we conducted an extensive search across 7 electronic databases, encompassing all pertinent animal studies for a systematic review and meta-analysis. Methodological quality was evaluated using SYRCLE’s bias risk tool, with statistical analysis performed using Stata 17.0. The primary outcome measures included the survival of retinal ganglion cells and retinal thickness.ResultsThe comprehensive analysis of the 30 included studies revealed that resveratrol can enhance the expression of Sirtuin 1(SIRT1) protein in retinal tissue (SMD: 3.00, 95% CI: 2.46, 3.53, P = 0.095), boost the survival rate of retinal ganglion cells (SMD: 4.33, 95% CI: 3.28, 5.38, P < 0.05), decelerate the thinning of retinal thickness (SMD: 4.26, 95% CI: 2.77, 5.75, P < 0.05), and enhance visual function. Its potential mechanism of action may involve the suppression of pro-inflammatory cytokine levels and cell apoptosis.DiscussionResveratrol emerges as a promising agent for mitigating glaucoma-related retinal damage. However, given that the animal research models utilized in the study may not fully reflect the intricate scenarios of multiple coexisting diseases in clinical settings, and the administration methods in animal models may differ from those in clinical practice, future studies should aim to provide higher levels of evidence to facilitate the clinical translation of these findings.Systematic Review Registration:identifier [CRD42024535673].